Anti-Poverty Income Transfers in the US - A Framework for the Evaluation of Policy Reforms - Nawid Siassi; Salvador Ortigueira (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
In this paper, we present a dynamic model of labor supply, consumption, savings and marital decisions where we embed the income tax schedule and the four main anti-poverty income transfer programs in the U.S. The model is calibrated to match moments from a sample of non-college-educated workers with children in the 2014 Annual Social and Economic Supplement of the Current Population Survey. We then use the model to assess the effects of three recent proposals to reform the U.S. tax-transfer system, and especially to ameliorate the disincentives introduced by the current EITC schedule to married mothers' labor force participation. The categorical and economic conditions for eligibility and benefits of the transfer programs, along with the income and payroll tax system, yield complex budget constraints and introduce a web of interactions whose effects we aim to understand and quantify.
Keywords: E21; H24; H31; 330